Kinetics of extraction from water solutions of Fe3+, Cu2+ and Pb2+ + ions by filter loading, obtained by blinding plasters - A. I. Teran (Литьë и металлургия, 2020)
In this study, we investigated the kinetics of extraction from aqueous solutions of Fe3+, Cu2+ and Pb2+ by filter loadings, derived from the steelmaking slags. A formal kinetic approach based on the relationship between the relative deposition rate (α) and time (τ) was used to estimate the mechanism and kinetic parameters of the deposition process). From the set of equations are selected those that in a given region of the degree of completion of the process gave the minimum value of the variance, that is, described the process in the system at this stage with the maximum probability. Three models that best correspond to real processes are selected. It was found that the deposition process at the initial stage limits the chemical stage of nucleation (formation of crystalline precipitate), then – the reaction at the interface (formation of a continuous layer of reaction products on the surface of the nuclei), and at the final stage – the growth of a continuous layer of reaction products.